The Eph/ephrin system symphony of gut inflammation - Peishan Qiu; Daojiang Li; Cong Xiao; Fei Xu; Xiaoyu Chen; Ying Chang; Lan Liu; Lei Zhang; Qiu Zhao; Yuhua Chen (Pharmacological Research, 2023)
The extent of gut inflammation depends largely on the gut barrier’s integrity and enteric neuroimmune interactions. However, the factors and molecular mechanisms that regulate inflammation-related changes in the enteric nervous system (ENS) remain largely unexplored. Eph/ephrin signaling is critical for inflammatory response, neuronal activation, and synaptic plasticity in the brain, but its presence and function in the ENS have been largely unknown to date. This review discusses the critical role of Eph/ephrin in regulating gut homeostasis, inflammation, neuroimmune interactions, and pain pathways. Targeting the Eph/ephrin system offers innovative treatments for gut inflammation disorders, offering hope for enhanced patient prognosis, pain management, and overall quality of life.